2010
DOI: 10.1002/ijc.25651
|View full text |Cite
|
Sign up to set email alerts
|

Integrated genetic and epigenetic analysis of bladder cancer reveals an additive diagnostic value of FGFR3 mutations and hypermethylation events

Abstract: The bladder cancer genome harbors numerous oncogenic mutations and aberrantly methylated gene promoters. The aim of our study was to generate a profile of these alterations and investigate their use as biomarkers in urine sediments for noninvasive detection of bladder cancer. We systematically screened FGFR3, PIK3CA, TP53, HRAS, NRAS and KRAS for mutations and quantitatively assessed the methylation status of APC, ARF, DBC1, INK4A, RARB, RASSF1A, SFRP1, SFRP2, SFRP4, SFRP5 and WIF1 in a prospective series of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
99
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(102 citation statements)
references
References 47 publications
(64 reference statements)
2
99
0
Order By: Relevance
“…Our three-gene methylation panel consisting of OTX1, ONECUT2, and OSR1 had a sensitivity of 68% and 74% in the test and validation set respectively with a specificity of 90% for the detection of recurrent bladder tumors in voided urine. Previously, we and Serizawa and colleagues, (34) showed an inverse correlation between FGFR3 mutation and methylation, therefore a combination of these assays could increase sensitivity for the detection of recurrent bladder cancer. We therefore combined the 3-plex methylation assay with the FGFR3 mutation assay.…”
Section: Discussionmentioning
confidence: 82%
“…Our three-gene methylation panel consisting of OTX1, ONECUT2, and OSR1 had a sensitivity of 68% and 74% in the test and validation set respectively with a specificity of 90% for the detection of recurrent bladder tumors in voided urine. Previously, we and Serizawa and colleagues, (34) showed an inverse correlation between FGFR3 mutation and methylation, therefore a combination of these assays could increase sensitivity for the detection of recurrent bladder cancer. We therefore combined the 3-plex methylation assay with the FGFR3 mutation assay.…”
Section: Discussionmentioning
confidence: 82%
“…Of the 63 reports selected for detailed evaluation, 33 were excluded as duplications or because they lacked key data. The final meta-analysis was carried out on the remaining 30 studies (Billerey et al, 2001;Kimura et al, 2001;Bakkar et al, 2003;Rieger-Christ et al, 2003;van Rhijn et al, 2003van Rhijn et al, , 2004Hernández et al, 2005;Jebar et al, 2005;van der Aa et al, 2005;Wallerand et al, 2005;Hernández et al, 2006;Lindgren et al, 2006;Tomlinson et al, 2007;van Oers et al, 2007;Burger et al, 2008;Junker et al, 2008;Eltze et al, 2009;Ouerhani et al, 2009;van Oers et al, 2009;Zieger et al, 2009;Bakkar et al, 2010;Bodoor et al, 2010;Kompier et al, 2010;Miyake et al, 2010;van Rhijn et al, 2010;Al-Ahmadie et al, 2011;Dodurga et al, 2011;Serizawa et al, 2011;Sjödahl et al, 2011;van Rhijn et al, 2012). Twenty-five of the studies (Table 1A) investigated the association between FGFR3 mutations and grade or stage, while the other 13 studies (Table 1B) investigated the prognostic value of FGFR3 mutations for BC.…”
Section: Resultsmentioning
confidence: 99%
“…Many genes have been reported to be hypermethylated in bladder cancer, but it is just recently that studies with new screening approaches have identified methylation markers with high sensitivity and specificity (14,34,35,39,40). Using the Infinium array, we identified genes being hypoor hypermethylated in bladder cancer (Supplementary Table S10).…”
Section: Discussionmentioning
confidence: 99%
“…All studies mentioned above have a higher sensitivity than cytology and specificity equal or slightly lower than cytology. One way of improving the already sensitive bladder cancer detection assay is to combine methylation and mutational analysis as done by Serizawa and colleagues (35). In their study, they discovered an inverse correlation between methylation and FGFR3 mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation